2020
DOI: 10.1016/j.jrid.2020.03.004
|View full text |Cite
|
Sign up to set email alerts
|

A mild type of childhood Covid-19 - A case report

Abstract: Since January 2020 Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Forty‐six articles met the inclusion and exclusion criteria and were analyzed for the systemic review (Figure 1). 13‐58 The study characteristics and results of the systematic review are demonstrated in Table 1. All the included articles were published from 1 February 2020 to 20 June 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Forty‐six articles met the inclusion and exclusion criteria and were analyzed for the systemic review (Figure 1). 13‐58 The study characteristics and results of the systematic review are demonstrated in Table 1. All the included articles were published from 1 February 2020 to 20 June 2020.…”
Section: Resultsmentioning
confidence: 99%
“…We also performed a chest x-ray and no infiltrates or pleural effusion were found. This finding is appropriate with study from Xiaoping et al in China, found no obvious abnormality in chest X-ray from pediatric patients nine-years-old with COVID-19 [ 12 ]. Abnormal respiratory findings might be small pleural effusions, patchy consolidations, focal consolidation, and atelectasis [ 8 ].…”
Section: Discussionmentioning
confidence: 52%
“…Xing et al, (30) 1 -6y Family transmission NS Yes/NS Yin et al, (31) 9y NS NS Yes/NS Chen et al, (32) 7m -17y Travel history and community transmission NS Yes/NS Morey-Olivé et al, (33) 2m e 6y Community transmission Cholestatic liver disease Yes/NS Liu et al, (34) 11m -9y Community transmission NS NS Chacón-Aguilar et al, (35) 26d NS NS Yes/06 Ji et al, (36) 9 e 15y Travel history No Yes/02…”
Section: Age Group Probable Contamination Of the Disease Pre-existing Disease/condition Hospitalization/ Length (Days)mentioning
confidence: 99%